PENGARUH ROLE STRESS, GOOD GOVERNANCE, GAJI AUDITOR TERHADAP KINERJA AUDITOR DAN KECERDASAN EMOSIONAL SEBAGAI PEMODERASI - Nisei, Bella Dwi Amalistie; Trisnawati, Estralita (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This research aims to find out whether role stress, good governance, auditor salary have an effect on auditor performance and emotional intelligence as a moderator. This research used a purposive sampling technique to determine a sample of 54 respondents. This research uses a qualitative approach and questionnaires as research instruments with the research object being practitioners' perceptions of auditors in South Jakarta. Hypothesis testing was carried out using multiple linear regression tests using IBM SPSS 26. The results of this study showed that role stress and good governance did not have a significant effect, while auditor salary had a significant effect on auditor performance and emotional intelligence moderated auditor salary and good governance had a significant effect on auditor performance. This research suggests to future researchers to add variables of gender, age, educational background, and length of service as proven by this research that these criteria have a significant effect and can explain the dependent variable. For further research, you can refer to this research as a source of literature regarding references, knowledge and information about the importance of role stress, good governance and auditor salary on auditor performance and emotional intelligence as a moderator.